Poverty, Unemployment, and HDI Impact on ASEAN Economic Growth: An Islamic Approach - Pratomo, Dimas; Oktanira, Celsi; Kurniawan, Muhammad; Ar-Royyan Ramly (Jeksyah: Islamic Economics Journal, 2024)
This study aims to investigate the relationship between the Human Development Index (HDI), the Poverty Rate, and the Unemployment Rate in five ASEAN countries between 2018 and 2022 from an Islamic economic perspective. This research is quantitative in nature and uses panel data, which is a combination of cross-sectional and time series data. The cross-sectional data in this study covers five ASEAN countries, while the time series data spans the last five years, from 2018 to 2022. Panel regression analysis was conducted using the Random Effect Model, which is the best model, with the assistance of the E-views 12 program. The study's population includes all ASEAN countries. Purposive sampling technique was used in this study, with the selection criteria being the five countries with the highest per capita income in 2022. The study's results indicate that the variables of unemployment, poverty, and HDI simultaneously affect economic growth. Poverty has a negative and significant impact on economic growth. Unemployment has a negative but not significant impact on economic growth. Additionally, HDI has a positive and significant impact on economic growth. From an Islamic perspective, economic growth is seen as a tool for enhancing both material and spiritual welfare, aligning with Sharia principles and emphasizing justice and holistic development.